STRATEGI PENYULUH KESEHATAN DALAM MENGURANGI STUNTING PADA ANAK DI PUSKESMAS TAROWANG KECAMATAN TAROWANG KABUPATEN JENEPONTO - Abdul Rauf Jabal; M Sattu Alang; St. Rahmatiah (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam, 2022)
This research raises the main problem of "Health Extension Strategies in Reducing Stunting in Children at the Tarowang Health Center, Tarowang District, Jeneponto Regency", with sub-problems namely: 1. How is the Health Extension Method in Reducing Stunting in Children at the Tarowang Health Center, Tarowang District, Jeneponto Regency? And What are the Obstacles to Health Extension in Reducing Stuntimg in Children at the Tarowang Health Center, Tarowang District, Jeneponto Regency? This research uses descriptive qualitative research located in Tarowang Health Center, Tarowang District, Jeneponto Regency. The research approach used is the guidance approach. The primary data source of this writing is Yuki Meista Indari as a Health Extension Worker (key informant), additional informants are the Head of the Puskesmas, Puskesmas Midwife, Village Head, District Village Assistant (Pd), Parents of Children. Secondary data sources are books, theses, journals, literature, other data sources that can be used as a complement. Data collection methods are observation, interview, and documentation. Data analysis was carried out with three stages, namely data reduction, data presentation, and conclusion drawing. Based on the results of this study, it shows that the Health Extension Method in Reducing Stunting in Children at Tarowang Health Center, Tarowang District, Jeneponto Regency, namely: Routine pregnancy checks, Ensuring adequate nutrition for mothers and babies, Exclusive breastfeeding, Providing complete immunization, Socializing the dangers of stunting. The implication of this research is that it is hoped that all health educators will utilize the data and information in this health profile to improve the quality of health development whose benefits can be felt by the community, especially in the working area of the Tarowang Health Center, Tarowang District, Jeneponto Regency.